Evaluating the Role of E-Commerce in Economic Growth - Rashid, Farhad Naseraldeen (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
E-commerce is an important and interactive factor for the country’s economic growth and the strengthening of internal and external trade, it is also an important factor in increasing the marketing competition level for goods and services, also reducing administrative and communication costs, and it is the center for marketing on the Internet via direct relationship between the customer and seller. The main aim of the research is to evaluate the e-commerce role and its impact on economic growth in the city of Slemani. To achieve this goal, the research depended on the questionnaire-form which consisted of (200) forms distributed in different areas in Slemani city, thereafter; analysis of the answers was made by the mean of the (SPSS 23) program. The research has reached some results, and the most important of them is that e-commerce is a good support for delivering project production to the market quickly and with less costs. Also, the research suggests to take-care of building an electronic bank so as to develop e-commerce in the Slemani city because it is a main base for the development of this trade.